(untitled) (Bangladesh Journal of Zoology, 2019)
Hilsa shad (Tenualosa ilisha) belonging to the family Clupeidae is a diadromous migratory fish species. It is an important fish in the countries bordering to the Bay of Bengal. Bangladesh harvest about 60% of world hilsa catch. Hilsa contributed12.9% of the country’s total fish production in 2017-2018 with an estimated annual production of 517,198 tons, which was 1.0% to the GDP to support livelihoods of 1.2 million hilsa fishers of Bangladesh. In spite of the importance, there was an alarming situation in hilsa production, where over fishing of hilsa with a result of decline in inland production were observed. In the present study age and growth parameters L=57.7 cm total length and growth rate K=0.90 per year were calculated using VBGF growth function. Population parameters Z=4.90 were calculated using length converted catch curve, M (at water temperature 27°C) =1.45 using Pauly’s formula, F=1.09 and E=70 were estimated. Results indicates both recruitment overfishing and growth over fishing occur through indiscriminate fishing of juvenile hilsa (Jatka) as wel as brood hilsa(mother). Fishing effort has to be reduced at any cost and the affected fishers should be rehabilitated in a proper manner for obtaining the sustainable production of hilsa resources. Bangladesh J. Zool. 47(1): 173-183, 2019